Enhancing Formal Modelling Tool Support with Increased Automation - Lausdahl, Kenneth (Technical Report Electronics and Computer Engineering, 2012)
Progress report for the qualification exam report for PhD Student Kenneth Lausdahl. Initial work on enhancing tool support for the formal method VDM and the concept of unifying a abstract syntax tree with the ability for isolated extensions is described. The tool support includes a connection to UML and a test automation principle based on traces written as a kind of regular expressions.